Disciplining Christians: correction and community in Augustine's letters - Ebbeler, Jennifer (Oxford studies in late antiquity, 2012)
Corrective correspondences -- Augustine's epistolary corpus -- Caveat lector -- Latin prose epistolography -- Interpreting Augustine's correspondence -- A note on terminology -- Rebuke, friendship, and community -- Experiments in epistolary correction -- The honeyed sword : rebuking Jerome -- The Donatists and the limits of the corrective correspondence -- The retrospective correction of Pelagius -- The paper trail